Vokal Tradisi Batak Toba “Andung” - Stevanie Lumbangaol; Uus Karwati; Diah Latifah (Universitas Negeri Medan, 2019)
In the current era of globalization, learning is often associated with local wisdom. The local cultural base is indeed very important, because national character is formed from cultural roots. Therefore many have raised local culture and wisdom as a basis for learning. Likewise, in the Music Education Study Program, one course is presented, namely Vocal Tradition of the Archipelago, in which there is material in the Toba Batak Tradition Vocal, Andung. Through this course,